Role of the music festival thyagaraja aradhana in shaping the town of Thiruvaiyaru Tamil Nadu - Saralaya, Anagha Keshava (School of Planning and Architecture, 2023)
The identity of a place is shaped by a sound balance between dynamic and static components, people and urban activities, which are essentially interrelated – imparting distinctiveness to the place. Music and landscapes in India seem to be interwoven with each other. There are numerous classical music festivals held throughout India, of which, a few hold great significance – given the set of traditions put forth by them, their historic character, engagement with people and relationship with the spaces associated – enhancing the quality of the classical art and encouraging participation from both within and outside the musical fraternity. ‘Thyagaraja Aradhana’ in Thiruvaiyaru is one such example, set on the banks of river Kaveri. ‘Thyagaraja Aradhana’ is celebrated every year on the death anniversary of Saint Sri Thyagaraja at his samadhi at Thiruvaiyaru in Tamil Nadu. A vaggeyakara1 of highest stature, Sri Thyagaraja was integral and influential in the development of India's classical music tradition. This music festival is undoubtedly the most important and highly revered in the community of Carnatic Classical Music. The thesis is focussed on studying the town of Thiruvaiyaru and understanding the role of ‘Thyagaraja Aradhana’ in shaping the town. Documentation of the music festival is an aspect of the study. The reciprocal relationship between the town and the music festival is explored through various analyses. The significance of ‘Thiruvaiyaru Thyagaraja Aradhana’ is established thereby.
Keywords: Kaveri delta; Indian classical music; Cultural landscape